Isolasi dan Karakterisasi Bakteri Alkali-Proteolitik Sumber Air Panas Semurup Kerinci Jambi - Yurike Nova Edlin; Anthoni Agustien; Djong Hon Tjong (Universitas Andalas, 2014)
Thermophile protease has economic value because this enzyme is useful on all kind of industry that used high temperature on it production process. In the effort of obtaining indigenous alkaline thermostable a protease bacterial that produce we explore potential hot spring at Semurup, Kerinci Jambi. This study was conducted from September 2013 to February 2014, Water samples were collected by purposive sampling, the character of thermophilic bacteria were described for each in laboratory of microbiology and biomolecular, development of biology, faculty of mathematic and natural science Andalas university, Padang. There were 40 thermophile colonies, 7 isolates showed alkali proteolytic index range from 0.3 to 2.00. SIII-10 isolate showed the highest in alkali proteolitic index. The characteristic of SIII-10 are: whute and bolt colony, gram negative, motil, positive sitrat agar and positive gelatin.Key words, Isolation, characterization, alkaline protease, thermostable, Hot spring.